Virtual Reality for the Support of School Teaching in the History Course - Carbajal, Benhur; Carreño, Yeferson; Burga, Daniel; Tello, Carlos [UNESP] (Springer Nature, 2025)
The article presents a virtual reality web application to enhance the teaching of history in high school students in Lima, Peru. It emphasizes the significance of supporting school teaching in light of the suboptimal educational outcomes in Latin America, as reflected in tests such as PISA. The state-of-the-art reviews virtual and augmented reality systems applied to education, such as games, simulations, and immersive environments. The motivation is the absence of a standard methodology to design effective VR experiences in education. The objective is to develop a web application with VR to improve the teaching of history in a school in Lima. The EduVR method is proposed, which uses the FrameVR platform to implement VR, with a client-server architecture and solid backend. The validation was performed with a case study in two groups of 15 students, one with traditional classes and the other additionally with VR. The VR group demonstrated an increase of 4 points on the exam versus 1 point without VR. The application was found to be easy to use by 93% of respondents, and 100% considered it very useful for learning. The main contribution is the EduVR method, which integrates VR to improve education. It can be concluded that the VR web application, when used in conjunction with traditional education, allows for a better understanding and retention of historical knowledge.
Keywords: education; history; methodology; teaching; virtual reality